Solving Partial Differential Equations by Homotopy Perturbation Method (Journal of the College of Basic Education, 2022)
In this paper, we submitted a good tool to solve linear and nonlinear partial differential equations which is called homotopy perturbation method. This method makes hard problems so easy to solve, in our paper we gave some various examples for linear and nonlinear partial differential equations by using this method.